Entre lugares comunes y el desconocimiento. Pandillas juveniles en una ciudad intermedia (Popayán, 2016-2018) - Gildardo Vanegas Muñoz; William Chará Ordóñez; Ana María Betancourt Ledezma (Revista Criminalidad)
This research article is an exploratory exercise that seeks to identify the socioeconomic conditions and contexts in which criminal activities associated with youth gangs in Popayán, capital of the Department of Cauca, are performed. To that end, we resorted to, on one hand, quantitative strategies based on statistical information from the National Police to describe the crimes of theft and brawls. On the other hand, data obtained from the Beneficiary Identification System (Sisben) was used to characterize the living conditions of Colombia’s juvenile population. Furthermore, qualitative strategies were used, in which documentary analysis stands out by means of press reviews and institutional documents, in order to know the actions being performed to attend to youth gangs. The analyzed information allowed cautioning that gangs are not exclusive expressions of large cities. Medium-sized cities are at the very center of crime and are a significant challenge to security and coexistence. However, beyond repressive intervention, there are few state initiatives related to this challenge and there is scant interest in understanding its complexity. Consequently, the situation’s effective possibilities of change are limited.